The impact of moderate and high intensity cardiovascular exertion on sub-elite soccer referee`s cognitive performance: A lab-based study - Senécal, I.; Howarth, S. J.; Wells, G. D.; Raymond, I.; Mior, S. (Journal of Sports Science & Medicine, 2021)
Soccer referees represent a specialized population who are required to perform decisional or perceptual tasks during physical exertion. Recent studies have demonstrated that submaximal acute exercise has a positive impact on cognitive performance. However, less is known about the impact of more strenuous exertion on cognitive performance. This study assessed the effect of moderate and maximal intensity exercise exertion on a cognitive performance in sub-elite soccer referees. Twelve experienced soccer referees (4 female, 8 male) were recruited. Data were collected on 2 separate days. Baseline fitness level was assessed by a standardized aerobic capacity test (VO2max Test) on Day 1, along with practice trials of the Stroop Color Word Test (Stroop Test) for evaluating cognitive performance. On Day 2, cognitive performance was assessed before, during, and after an incremental intensity exercise protocol based on the Fédération International de Football Association (FIFA) referee fitness test. Relative to results obtained at rest performance on the Stroop Test improved at moderate exertion and at maximal exertion during the modified FIFA fitness test (F = 18.97, p = .005). Mean time to completion (in seconds) of the interference Stroop task significantly improved (p < .05) between rest and moderate exertion [-3.0 ± 3.0 seconds] and between rest and maximal exertion [-4.8 ± 2.6 seconds]. In summary, we observed that cognitive performance was found to improve when sub-elite soccer referees performed moderate and maximal exercise relative to results obtained at rest. It is possible that referees focus their attention to improve goal-oriented processing in the brain during physical exertion.